DISCHARGE TEACHING TO IMPROVE DISCHARGE READINESS FOR PATIENTS POST HIP SURGERY: A LITERATURE REVIEW: DOI: https://doi.org/10.35654/ijnhs.v2i1.59 - Ina Nurul Rahmawati; Riri Maria (Alta Dharma Publisher, 2019)
The condition of returning home unpreparedness post hip surgery has an impact on the patient's ability after returning home. This unpreparedness is caused by the inability of patients to manage their own needs and care needs after returning home in carrying out daily tasks, caring for themselves, and the ability to do health care. So that a nursing strategy is needed in preparing the patient's discharge planning in the form of discharge teaching. Four data bases namely Cochrane, EBSCO, Google Scholar, and Scopus were used to explain the effect of discharge teaching to improve patient readiness post hip surgery. Educational needs expected by patients post hip surgery are related to complications, operating procedures, rehabilitation programs, prosthesis, and pain management. Patients hope to get knowledge related to all dimensions, but in reality they only get from the functional dimension. Patients get more knowledge only during treatment than when they are going home. Discharge teaching must also pay attention to the content of information and delivery methods and must be given in all stages of treatment and repetition of important items. So nurses are required to have competence and knowledge in carrying out discharge teaching with the aim of increasing patient readiness. Keywords: discharge teaching, discharge readiness, post hip surgery